Pure Hydrogen Production for Low Temperature Fuel Cells - Cornaglia, Laura Maria (2018)
The electric car industry is rapidly growing worldwide. There are two ways of providing the electricity needed in these vehicles, i.e. by means of either batteries or fuel cells. A reliable source of pure hydrogen is necessary for the latter alternative. Having in mind that the steam reforming of natural gas is at present the main source of this gas, different options for its production are discussed. This hydrogen needs further purification to get rid of the carbon monoxide (< 10 ppm) that irreversibly poisons the electrodes of the fuel cells. This work examines membrane reactors and hollow fiber membrane reactors. The latter are very attractive due to the severe mass (concentration polarization) and heat transport limitations that should be minimized at industrial scale. The work also presents examples of catalysts especially tailored for use in these applications. The main features of these formulations are high selectivity and stability. Their durability is directly connected with the sintering resistance and a very low activity to promote the formation of carbonaceous residues. The ultimate goal of this prospective contribution is to provide tools for the reader to evaluate present trends in research and the opportunities open in the field of H2 fuel production suitable for fuel cell cars.